Artempo : Where Time Becomes Art /. - Vervoordt, Axel; Visser, Mattijs (Ghent : Axel Vervoordt : MER. Paper Kunsthalle, 2007)
Abramovic, Marina ; El Anatsui ; Arman ; Artaud, Antonin ; Bacon, Francis ; Baerveldt, Erzsébet ; Bellmer, Hans ; Boetti, Alighiero ; Boltanski, Christian ; Borremans, Michaël ; Bourgeois, Louise ; Breton, André ; Buggenhout, Peter ; Burri, Alberto ; Guo-Qiang, Cai ; Castellani, Enrico ; Cecchini, Loris ; Cragg, Tony ; Davids, Yael ; de Bruyckere, Berlinde ; De Chirico, Giorgio ; Dubuffet, Jean ; Duchamps, Marcel ; Dumas, Marlene ; Fabre, Jan ; Filliou, Robert ; Fischli & Weiss ; Fontana, Lucio ; Fortuny, Mariano ; Giacometti, Alberto ; Graubner, Gotthard ; Grünfeld, Thomas ; Kapoor, Anish ; Kawara, On ; Kentridge, William ; Kimsooja ; Klein, Yves ; Lavier, Bertrand ; Lebel, Jean-Jacques ; Man Ray ; Manzoni, Piero ; Matta-Clark, Gordon ; Merz, Marisa ; Mezzaqui, Sabrina ; Miyajima, Tatsuo ; Molder, Jorge ; Motonaga, Sadamasa ; Münch, Klaus ; Murakami, Sabura ; Opalka, Roman ; Orlan ; Picasso, Pablo ; Piene, Otto ; Raetz, Markus ; Raushenberg, Robert ; Ross, Charles ; Rosso, Medardo ; Ruff, Thomas ; Shiraga, Kazuo ; Schütte, Thomas ; Stenvert, Curt ; Stroobant, Dominique ; Tsujimura, Shiro ; Tápies, Antoni ; Turrell, James ; Uecker, Gunther ; Vedova, Emilio ; Verheyen, Jef ; Warhol, Andy ; Wildt, Adolfo ; Yamazaki, Tsuruko
Artempo. Where Time Becomes Art, Palazzo Fortuny, Venezia, 9.06. - 7.10.2007
boek